2016
DOI: 10.1097/prs.0000000000001868
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells from Capillary Malformations Are Enriched for Somatic GNAQ Mutations

Abstract: Background A somatic mutation in GNAQ (c.548G>A;p.R183Q), encoding Gαq, has been found in syndromic and sporadic capillary malformation tissue. However, the specific cell type(s) containing the mutation is unknown. The purpose of this study was to determine which cell(s) in capillary malformations have the GNAQ mutation. Methods Human capillary malformation tissue was obtained from 13 patients during a clinically-indicated procedure. Droplet digital PCR (ddPCR), capable of detecting mutant allelic frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 12 publications
(13 reference statements)
7
112
3
Order By: Relevance
“…Primers and probes were designed to target GNAQ p.R183Q as described previously 10 . Sequences used were: forward primer (5′-CCTGCCTACGCAACAAGAT-3′); reverse primer (5′-GTAAGTCAAAGGGGTATTCGAT-3′); reference probe (5′-TGCTTAGAGTTCGAGTCCCCACC-3′); mutant probe (5′-TGCTTAGAGTTCAAGTCCCCACC-3′).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers and probes were designed to target GNAQ p.R183Q as described previously 10 . Sequences used were: forward primer (5′-CCTGCCTACGCAACAAGAT-3′); reverse primer (5′-GTAAGTCAAAGGGGTATTCGAT-3′); reference probe (5′-TGCTTAGAGTTCGAGTCCCCACC-3′); mutant probe (5′-TGCTTAGAGTTCAAGTCCCCACC-3′).…”
Section: Methodsmentioning
confidence: 99%
“…The p.R183Q mutation impairs GTPase activity and maintains Gαq in its GTP–bound, active state 9 . Our laboratory recently showed that the GNAQ p.R183Q mutation is enriched in the endothelial cell population in SWS skin lesions and sporadic capillary malformations 10 . Another group reported GNAQ p.R183Q mutant cells located around blood vessels in port-wine stains 11 .…”
Section: Introductionmentioning
confidence: 99%
“…These same somatic mosaic mutations have been identified in cancers, vascular malformations, and other disorders with overgrowth (4,7,9). In the present study, we sought to determine if overgrowth in patients with FIL was caused by a somatic mutation in one tissue type (subcutaneous adipose) that exerts paracrine effects on neighboring structures (10)or by the presence of mutant cells in each of a patient's overgrown tissues (11).…”
Section: Discussionmentioning
confidence: 99%
“…Our identification of GNA14 mutations in KHEs, TAs, and LCHs-three distinct classes of vascular tumors-also highlights the pleiotropy of G aq variants, as seen in GNAQ and GNA11 mutations causing LCHs, PWSs, and NICHs. [10][11][12]16,19 Similarly, activating mutations in HRAS, KRAS, and NRAS also demonstrate phenotypic heterogeneity within vascular anomalies, giving rise to both LCHs and NICHs. 8,9 It remains unclear how identical somatic mutations can give rise to distinct clinical phenotypes.…”
Section: 34mentioning
confidence: 99%
“…This mutation has not been previously identified in vascular tumors, although somatic mutation c.548G>A (p.Arg183Gln) in paralog GNAQ is common in capillary malformations and PWSs and has been found in a single case of secondary LCH arising within a PWS. 8,12,19 A recent survey of 16 congenital hemangiomas identified 12/16 (75%) lesions with GNA11 and GNAQ mutations, but all were Pro or Leu substitutions at Gln209. 10 We further analyzed subjects without a detected mutation.…”
mentioning
confidence: 99%